Physiological and molecular responses to thermal stress in red cusk-eel (Genypterus chilensis) juveniles reveals atrophy and oxidative damage in skeletal muscle. (December 2020) - Dettleff, Phillip; Zuloaga, Rodrigo; Fuentes, Marcia; Gonzalez, Pamela; Aedo, Jorge; Estrada, Juan Manuel; Molina, Alfredo; Valdés, Juan Antonio
Abstract: The red cusk-eel ( Genypterus chilensis ) is a native species with strong potential to support Chilean aquaculture diversification. Environmental stressors, such as temperature, may generate important effects in fish physiology with negative impact. However, no information exists on the effects of thermal stress in Genypterus species or how this stressor affects the skeletal muscle. The present study evaluated for the first time the effect of high temperature stress in red cusk-eel juveniles to determine changes in plasmatic markers of stress (cortisol, glucose and lactate dehydrogenase (LDH)), the transcriptional effect in skeletal muscle genes related to (i) heat shock protein response ( hsp60 and hsp70 ), (ii) muscle atrophy and growth ( foxo1, foxo3, fbxo32, murf-1, myod1 and ddit4 ), and (iii) oxidative stress ( cat, sod1 and gpx1 ), and evaluate the DNA damage (AP sites) and peroxidative damage (lipid peroxidation (HNE proteins)) in this tissue. Thermal stress generates a significant increase in plasmatic levels of cortisol, glucose and LDH activity and induced heat shock protein transcripts in muscle. We also observed an upregulation of atrophy-related genes ( foxo1, foxo3 and fbxo32 ) and a significant modulation of growth-related genes ( myod1 and ddit4 ). Thermal stress induced oxidative stress in skeletal muscle, as represented by the upregulation of antioxidant genes ( cat and sod1 ) and a significant increase in DNA damage and lipid peroxidation. The present study provides the first physiological and molecular information of the effects of thermal stress on skeletal muscle in a Genypterus species, which should be considered in a climate change scenario. Highlights: High water temperature generate thermal stress on red cusk-eel juveniles. Thermal stress increase cortisol and glucose levels and LDH activity in plasma. Upregulation of hsp60 and hsp70 in muscle in response to thermal stress. Modulation of atrophy-related and growth-related genes in skeletal muscle. Thermal stress induced oxidative stress and damage in muscle on red cusk-eel.